2018
DOI: 10.1093/ibd/izx101
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Quadrivalent Influenza Vaccine for Patients with Inflammatory Bowel Disease Undergoing Immunosuppressive Therapy

Abstract: Single dose QIV showed sufficient immunogenicity in patients with inflammatory bowel disease, and a boost in immunization by additional vaccination was not obtained. Additionally, immunogenicity was low in patients receiving infliximab therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 27 publications
3
41
0
Order By: Relevance
“…Although antibody titers only increase slightly after repeated annual influenza vaccination, they still prevent laboratory proven influenza infections [ 35 ]. Several previous studies have shown decreased immune responses to influenza vaccination in IBD patients using anti-TNFα agents [ 6 , 7 , 11 , 12 , 13 ]. This is in line with our results from the HI assay, but not reflected by our T-cell proliferation data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although antibody titers only increase slightly after repeated annual influenza vaccination, they still prevent laboratory proven influenza infections [ 35 ]. Several previous studies have shown decreased immune responses to influenza vaccination in IBD patients using anti-TNFα agents [ 6 , 7 , 11 , 12 , 13 ]. This is in line with our results from the HI assay, but not reflected by our T-cell proliferation data.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination against influenza reduces the risk of infection in immunocompromised patients [ 4 ]. However, influenza vaccination may be less effective in patients treated with immunosuppressive therapies [ 5 , 6 , 7 ] and immunological mechanisms of the impaired vaccination response in IBD patients are often poorly understood [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the MHRA does not list immunosuppression as a contraindication to the BNT162b2, ChAdOx1 nCoV-19, or mRNA-1273 vaccines, it does indicate that there is a theoretical possibility that immunosuppressive drugs could reduce the effectiveness of the vaccines, based on evidence from studies looking at the effect of immunosuppression on the immunogenicity of vaccines used for other infectious diseases ( figure 2 ). Infliximab monotherapy is linked to impaired induction of protective immunity following hepatitis B virus (HBV), 16 hepatitis A virus (HAV), 17 pneumococcal, 14 , 21 and influenza 18 , 22 , 23 vaccination, which might be more pronounced when anti-TNF therapy is combined with immunomodulators such as thiopurines or methotrexate. 24 , 25 Vedolizumab, which has a gut-specific mechanism of action, does not hinder HBV or influenza vaccination, but is associated with impaired antibody responses to cholera toxin, administered orally.…”
Section: Introductionmentioning
confidence: 99%
“…No substantial humoral response No need to alter therapy for vaccination; administer vaccine irrespective of last dose 8,[12][13][14][15]…”
mentioning
confidence: 99%